Guided Growth Procedures: Broken Tension Band Implants in Patients With Blount Disease. Issue 5 (24th May 2022) - Chapman, Paige; Dueber, David M.; Stephenson, Lindsay P.; Scott, Allison C.; Lerman, Joel A.; Powell, Kenneth P.; Nossov, Sarah B.; Franklin, Corinna C.; Westberry, David E.; Ackman, Jeffery D.; Walker, Janet L.
Abstract : Background: Tension band plate and screw implants (TBI) are frequently used for temporary hemiepiphyseodeses to manage angular deformity in growing children. The reported implant breakage rate, when TBI is used for deformities in patients with Blount disease, is much higher than when used in other diagnoses. Our hypothesis is that perioperative factors can identify risks for TBI breakage. Methods: A retrospective case-control study was performed of 246 TBI procedures in 113 patients with Blount disease at 8 tertiary pediatric orthopaedic centers from 2008 to 2018. Patient demographics, age at diagnosis, weight, body mass index (BMI), radiographic deformity severity measures, location, and types of implants were studied. The outcome of implant breakage was compared with these perioperative factors using univariate logistic regression with Bonferroni correction for multiplicity to significance tests. Results: There were 30 broken implants (12%), failing at mean 1.6 years following implantation. Most failures involved the metaphyseal screws. Increased BMI was associated with increased implant breakage. Increased varus deformity was directly associated with greater implant breakage and may be a more important factor in failure for those below 7 years compared with those 8 years or above at diagnosis. There was a 50% breakage rate for TBI with solid 3.5 mm screws in Blount disease with onset 8 years or above of age. No demographic or implant factors were found to be significant. Conclusions: Breakage of TBI was associated with increased BMI and varus deformity in patients with Blount disease. Larger studies are required to determine the relative contribution and limits of each parameter. Solid 3.5 mm screws should be used with caution in TBI for late-onset Blount disease. Level of Evidence: Level III.